2019
DOI: 10.1002/jcb.28554
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential hub‐lncRNAs in ischemic stroke based on Subpathway‐LNCE method

Abstract: Ischemic stroke is a devastating condition with a high burden of neurological disability and death. The aim of this study was to explore the potential long noncoding RNA (lncRNA) biomarkers underlying the mechanism of stroke. The Subpathway-LNCE method, which was specifically designed to identify lncRNAs competitively regulated functions in diseases, was applied in ischemic stroke dataset to identify ischemic-stroke-associated dysfunctional subpathway that regulated by lncRNAs. At first, based on the shared mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…26 A previous report proposed that downregulated NEXN-AS1 might act as a vital biomarker in ischemic stroke. 27 Intriguingly, a recent document manifested that high level of NEXN-AS1 retarded AS progression through repression of adhesion molecules expression and inammatory cytokines secretion by regulating NEXN. 18 These ndings from our study described above prompted us to explore NEXN-AS1 as a potential regulator on VSMC proliferation and migration in AS progression.…”
Section: Discussionmentioning
confidence: 99%
“…26 A previous report proposed that downregulated NEXN-AS1 might act as a vital biomarker in ischemic stroke. 27 Intriguingly, a recent document manifested that high level of NEXN-AS1 retarded AS progression through repression of adhesion molecules expression and inammatory cytokines secretion by regulating NEXN. 18 These ndings from our study described above prompted us to explore NEXN-AS1 as a potential regulator on VSMC proliferation and migration in AS progression.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that lncRNAs are non-coding segments of RNAs that have notable regulatory functions in the pathophysiological processes of multiple diseases, including OA (13)(14)(15). LINC00473, a novel lncRNA, has been revealed to be upregulated in several diseases, such as ischemic stroke and preeclampsia (16,17). Moreover, LINC00473 is upregulated in patients with severe pain associated with OA (18).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have revealed that long intergenic non-protein coding RNA 473 (LINC00473) serves a notable role in various diseases. For example, LINC00473 has been identified as a notable biomarker in ischemic stroke through the subpathway-LNCE method, which was designed to identify lncRNAs that competitively modulated functions in diseases (16). LINC00473 downregulation contributes to the development of preeclampsia (17).…”
Section: Introductionmentioning
confidence: 99%
“…linc-DHFRL1-4, SNHG15, and linc-FAM98A-3 are suggested as biomarkers for the detection of acute IS (Deng et al 2018). Zheng et al (2019) proposed that five lncRNAs, including LINC00265, LINC00473, NEXN-AS1, HCG17, and MEG8, could be considered as important lncRNA biomarkers in IS. In the present study, the area under the ROC curve (AUC) indicated that measuring RUNX1-IT1 in peripheral blood is not suitable for diagnostic purposes in LAA (AUC = 0.609 ± 0.04, sensitivity = 0.59, specificity = 0.61) ( Fig.…”
Section: Discussionmentioning
confidence: 99%